The Effectiveness of Online Learning Using Online Media in Basic Programming Subjects - Tajura Jura (Universitas Pendidikan Indonesia, 2021)
This study aims to determine the effectiveness of online learning using online media during the COVID-19 pandemic in basic programming subjects. This research is descriptive quantitative research that focuses on evaluating learning using online media. The study population is all students of SMK Negeri 2 Bandung who are taught basic programming subjects using online methods. The research sample was students of grade X TKI 1 SMK Negeri 2 Bandung who were selected using a simple random sampling technique by considering population homogeneity. The data collection instrument used an online learning questionnaire. Data analysis using descriptive statistics. The results suggest that learning basic programming using online media is “very effective” (23.3%), most of them rated it “effective” (46.7%), and rated it “mediocre” (20%). There are also learners who consider online learning “ineffective” (10%), and no one rate it “very ineffective” (0%). Finally, to improve the quality of basic programming online learning during the COVID-19 pandemic, educators must fulfill some suggestions from respondents, namely: (1) learning is carried out through online media; (2) provision of concise learning materials; (3) minimize sending materials in the form of files to save quota; (4) The selection of material in the file must be based on easy-to-understand language criteria.